Automated System – Application Of AHP And Topsis Analysis For Productivity Improvement - Yakop, Mohd Halim (2018)
Productivity improvement in manufacturing industry is always the key focus to strengthen an enterprise cost position to stay ahead of competition. Increase in productivity can reduce the cost of work on the production unit or an increase in output. This study emphasises on enhancing the work method in food industry by proposing an automated practice that is imposed to eliminate waste activities for continuous improvement. Additionally, this study focuses at lekor shaping process in Zazihan Enterprise. The production report showed that the company is having a shortage for cheesy lekor ball due to low production rate compared to targeted demand. The objective of this study is to analyse the current method by using work study and identify all activities related to the shaping process for cheesy lekor ball. Apparently, based on multiple-criteria requirement, AHP and TOPSIS analysis were used to determine the best automated machine for the shaping process of replacing a manual method. Finally, the proposed method was evaluated, and the results indicated that the productivity improvement rate is increased by 860% which is from 45 to 432 bulk per week. Moreover, the number of worker has been reduced as the proposed method only requires a single person to operate while other workers can focus on producing different types of products at the same time.